2017
DOI: 10.3389/fnhum.2017.00451
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reference Emerges Earlier than Emotion during an Implicit Self-Referential Emotion Processing Task: Event-Related Potential Evidence

Abstract: Self-referential emotion refers to the process of evaluating emotional stimuli with respect to the self. Processes indicative of a self-positivity bias are reflected in electroencephalogram (EEG) signals at ~400 ms when the task does not require a discrimination of self from other. However, when distinguishing between self-referential and other-referential emotions is required, previous studies have shown inconsistent temporal dynamics of EEG signals in slightly different tasks. Based on the observation of ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 68 publications
1
11
2
Order By: Relevance
“…Past studies investigating self-related affect in healthy groups have been ambiguous with regard to whether there should be a positivity (towards pleasant words) and negativity (towards unpleasant words) bias in the LPP response with some studies showing higher LPPs for pleasant compared to unpleasant self-referential words (e.g., Auerbach et al, 2015;Shestyuk & Deldin, 2010;Watson et al, 2007), while others show a self-related negativity bias of the kind we observed (e.g., Bernat, Bunce, & Shevrin, 2001;Fields & Kuperberg, 2012;Zhou et al, 2017).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Past studies investigating self-related affect in healthy groups have been ambiguous with regard to whether there should be a positivity (towards pleasant words) and negativity (towards unpleasant words) bias in the LPP response with some studies showing higher LPPs for pleasant compared to unpleasant self-referential words (e.g., Auerbach et al, 2015;Shestyuk & Deldin, 2010;Watson et al, 2007), while others show a self-related negativity bias of the kind we observed (e.g., Bernat, Bunce, & Shevrin, 2001;Fields & Kuperberg, 2012;Zhou et al, 2017).…”
Section: Discussioncontrasting
confidence: 66%
“…However, the findings are mixed. The P200 and LPP have been found to be both higher for pleasant compared to unpleasant self-referential words (Auerbach et al, 2015;Shestyuk & Deldin, 2010;Watson et al, 2007) as well as higher for 6 ERP of affective self-reference in meditators unpleasant compared to pleasant ones (Fields & Kuperberg, 2012;Zhou et al, 2017) in separate studies. ERP differences between pleasant and unpleasant words in the SRET have been used to identify brain patterns that differentiate healthy and clinical populations.…”
Section: Neural Correlates Of Self-referential Processingmentioning
confidence: 89%
See 1 more Smart Citation
“…LPPs for pleasant compared to unpleasant self-referential words (e.g., Auerbach et al, 2015;Shestyuk & Deldin, 2010;Watson et al, 2007), while others show a self-related negativity bias of the kind we observed (e.g., Bernat, Bunce, & Shevrin, 2001;Fields & Kuperberg, 2012;Zhou et al, 2017).…”
Section: Erp Of Affective Self-reference In Meditators 26supporting
confidence: 43%
“…However, the findings are mixed. The P200 and LPP have been found to be both higher for pleasant compared to unpleasant self-referential words (Auerbach et al, 2015;Shestyuk & Deldin, 2010;Watson et al, 2007) as well as higher for unpleasant compared to pleasant ones (Fields & Kuperberg, 2012;Zhou et al, 2017) in separate studies. ERP differences between pleasant and unpleasant words in the SRET have been used to identify brain patterns that differentiate healthy and clinical populations.…”
Section: Neural Correlates Of Self-referential Processingmentioning
confidence: 85%